2011
DOI: 10.1093/jac/dkr481
|View full text |Cite
|
Sign up to set email alerts
|

A novel phenicol exporter gene, fexB, found in enterococci of animal origin

Abstract: Objectives: To investigate two porcine Enterococcus isolates for the genetic basis of phenicol resistance and to determine the location and the genetic environment of the novel resistance gene.Methods: A total of 391 isolates with reduced florfenicol susceptibility (MIC ≥16 mg/L), obtained from 557 nasal swabs of individual pigs, were screened by PCR for the known florfenicol resistance genes. Isolates that were negative in these PCRs were analysed for their species assignment and antimicrobial susceptibility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 14 publications
3
53
0
Order By: Relevance
“…Along with ARG109, other residues such as GLN112 and GLY113 were also conserved in FexB protein. Motif-B was found to be important in the transfer of motif-B antiporters along with addition of protonation status with substrate binding in MdfA [13] and we predict a similar function for motif-B in FexB protein.…”
Section: Motif-bmentioning
confidence: 52%
See 4 more Smart Citations
“…Along with ARG109, other residues such as GLN112 and GLY113 were also conserved in FexB protein. Motif-B was found to be important in the transfer of motif-B antiporters along with addition of protonation status with substrate binding in MdfA [13] and we predict a similar function for motif-B in FexB protein.…”
Section: Motif-bmentioning
confidence: 52%
“…It is the only motif with membrane-embedded basic residue among MFS members which is also termed as 3D motif-B [13]. We observed that motif-B (R 109 mfQ 112 G 112 ) was also conserved in FexB protein (Fig.1) and is located on helix-5 (Fig.…”
Section: Motif-bmentioning
confidence: 82%
See 3 more Smart Citations